Differential Effects of Intranasal Vasopressin on the Processing of Adult and Infant Cues: An ERP Study - Wu, Xiaoyan; Xu, Pengfei; Luo, Yue-Jia; Feng, Chunliang (Frontiers in Human Neuroscience, 2018)
Arginine vasopressin (AVP) is a powerful regulator of various social behaviors across many species. However, seemingly contradictory effects of AVP have been found in both animal and human studies, e.g., promoting aggression on one hand and facilitating social bonding on the other hand. Therefore, we hypothesize that the role of AVP in social behaviors is context-dependent. To this end, we examined the modulatory effect of AVP on male’s behavioral and neural responses to infant and adult cues. After intranasal and double-blind treatment of AVP or placebo, male participants were asked to rate their subjective approaching willingness to infant and adult faces in specific contexts informed by cue words while EEG recording. Our results showed that AVP treatment increased approaching ratings to neutral and positive other-gender adult faces compared to emotional matched same-gender adult faces, and to negative girl faces compared to negative boy faces. Furthermore, compared to placebo treatment, AVP treatment induced larger N1 amplitudes to neutral cues associated with both adults and infants, whereas AVP treatment only sustained pronounced late positive potential (LPP) amplitudes to neutral cues of infants but not adults. Those findings implicate differential roles of AVP in the processing of adult- and infant-related cues and thus lend support to the context-dependent account.